Summation over Lower Index of Unsigned Stirling Numbers of the First Kind

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $n \in \Z_{\ge 0}$ be a positive integer.

Then:

$\displaystyle \sum_k \left[{n \atop k}\right] = n!$

where:

$\displaystyle \left[{n \atop k}\right]$ denotes an unsigned Stirling number of the first kind
$n!$ denotes the factorial of $n$.


Proof

The proof proceeds by induction on $n$.


For all $n \in \Z_{\ge 0}$, let $P \left({n}\right)$ be the proposition:

$\displaystyle \sum_k \left[{n \atop k}\right] = n!$


$P \left({0}\right)$ is the case:

\(\displaystyle \sum_k \left[{0 \atop k}\right]\) \(=\) \(\displaystyle \sum_k \delta_{0 k}\) Unsigned Stirling Number of the First Kind of 0
\(\displaystyle \) \(=\) \(\displaystyle 1\) all terms vanish but for $k = 0$
\(\displaystyle \) \(=\) \(\displaystyle 0!\) Definition of Factorial

Thus $P \left({0}\right)$ is seen to hold.


Basis for the Induction

$P \left({1}\right)$ is the case:

\(\displaystyle \sum_k \left[{1 \atop k}\right]\) \(=\) \(\displaystyle \sum_k \delta_{1 k}\) Unsigned Stirling Number of the First Kind of 1
\(\displaystyle \) \(=\) \(\displaystyle 1\) all terms vanish but for $k = 1$
\(\displaystyle \) \(=\) \(\displaystyle 1!\) Definition of Factorial

Thus $P \left({1}\right)$ is seen to hold.


This is the basis for the induction.


Induction Hypothesis

Now it needs to be shown that, if $P \left({m}\right)$ is true, where $m \ge 2$, then it logically follows that $P \left({m + 1}\right)$ is true.


So this is the induction hypothesis:

$\displaystyle \sum_k \left[{m \atop k}\right] = m!$


from which it is to be shown that:

$\displaystyle \sum_k \left[{m + 1 \atop k}\right] = \left({m + 1}\right)!$


Induction Step

This is the induction step:


\(\displaystyle \sum_k \left[{m + 1 \atop k}\right]\) \(=\) \(\displaystyle \sum_k \left({m \left[{m \atop k}\right] + \left[{m \atop k - 1}\right]}\right)\) Definition of Unsigned Stirling Numbers of the First Kind
\(\displaystyle \) \(=\) \(\displaystyle m \sum_k \left[{m \atop k}\right] + \sum_k \left[{m \atop k - 1}\right]\)
\(\displaystyle \) \(=\) \(\displaystyle m \sum_k \left[{m \atop k}\right] + \sum_k \left[{m \atop k}\right]\) Translation of Index Variable of Summation
\(\displaystyle \) \(=\) \(\displaystyle \left({m + 1}\right) \sum_k \left[{m \atop k}\right]\)
\(\displaystyle \) \(=\) \(\displaystyle \left({m + 1}\right) m!\) Induction Hypothesis
\(\displaystyle \) \(=\) \(\displaystyle \left({m + 1}\right)!\) Definition of Factorial


So $P \left({m}\right) \implies P \left({m + 1}\right)$ and the result follows by the Principle of Mathematical Induction.


Therefore:

$\displaystyle \forall n \in \Z_{\ge 0}: \sum_k \left[{n \atop k}\right] = n!$

$\blacksquare$


Sources